FACTORS AFFECTING FINANCIAL PERFORMANCE IN THE INFRASTRUCTURE INDUSTRY IN INDONESIA - Erica, Erica; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2023)
The company needs good governance in order for management to function properly and increase its performance. The separation of execution and oversight is an important characteristic of good governance. The aim of the research is to see if independent commissioners, CEO duality, committee size of committee audit, financial expertise on the audit committee board, and connection of political have an impact on business performance in infrastructure public companies in Indonesia during 2016 to 2020. Secondary data was used with 83 sample. The regression analysis used in this study was done using the SPSS version 25 application. The findings demonstrate that the audit committee size has a huge and beneficial impact on corporate performance. However, the independent board of commissioners, CEO duality, financial expertise on the audit committee, and political connections have no significance. The findings of the study indicate that the audit committees of Indonesian infrastructure corporations should be enhanced to compensate for the deficiencies of other governance elements.